MATHEMATICS HIGH SCHOOL

PLEASE ANSWER + BRAINLIEST!! What is the difference of the polynomials?

(12x^2 - 11y^2 - 13x)(5x^2 - 14y^2 - 9x)

A. 7x^2 + 3y^2 - 4x

B. 7x^2 - 3y^2 - 4x

C. 7x^2 - 25y^2 - 22x

D. 17x^2 - 25y^2 - 22x

Answers

Answer 1
Answer: (12-5)x² + (-11-(-14))y² + (-13-(-9))x =
  A. 7x² + 3y² - 4x

Related Questions

HIGH SCHOOL

If all the possible results are equally likely, what is the probability that a spin of the spinner will land on an upper case letter or g or f?

Answers

Answer: 1/3 or 1 out of 3 times

Step-by-step explanation: It seems as though there are only three options for it to land on, Upper case, g, and f-therefore you have a 1 in 3 chance for each

MIDDLE SCHOOL

PLEASE HELP ME:

Gala Apples cost $6.00 for 8 lbs. How much for 1 pound?

Answers

Answer:

$0.75

Step-by-step explanation:

6 divided by 8 = 0.75

0.75 times 8 = 6

HIGH SCHOOL

BRAINLIEST! What number must multiply each side of the equation 2/5x=10 to produce the equivalent equation x = 25? (NOTE: 2/5 IS A FRACTION) A. 1/5

B. 5/2

C.4

D.5

Answers

The number that we must use to multiply each side of the equation 2/5x = 10 to produce the equivalent equation x = 25 is; B: 5/2

We are given the equation;

(2/5)x = 10

  • Now, from multiplication property of equality, we know that;

Multiplying both sides by the same number is same as the original equation.

Thus, to make the left hand side only x, let us multiply both sides by the inverse of 2/5 which is 5/2 to get;

x = 10 × 5/2

x = 25

Read more on multiplication property of equality at; brainly.com/question/11455498

Answer:

Option B

Step-by-step explanation:

multiplying 2/5 with 5/2 will give 1 on the left hand side of the equation

multiplying 10 with 5/2 will give 25 on the right hand side of the equation, ultimately resulting in  x=25

MIDDLE SCHOOL

T + 5/8 = 15/16 i am confused

Answers

Answer:

Step-by-step explanation:

Subtract 5/8 from both sides:

Answer:

HIGH SCHOOL

The distance that a spring will stretch varies directly as the force applied to the spring. A force of 8080 pounds is needed to stretch a spring 88 inches. What force is required to stretch the spring 1919 ​inches? A nothing​-pound force is required to stretch the spring 1919 inches.

Answers

Answer:

176 199 pounds

Step-by-step explanation:

To answer this it is first useful to find the proportionality constant.

F= kx

8080 pounds = k.88 in

k = 91.81 pound/inch

So what force is required to stretch the spring to 1919 inches?

F = kx

  = 91.81 pound/inch * 1919 inches

  = 176 199 pounds

It is worth noting that this force seems rather large and the spring might have long reached its elastic limit

HIGH SCHOOL

Change to a fraction or mixed number in simplest form.
66 2/3% = _____.

Answers

66 2/3% means (66 2/3)/100
 as we knw%=100 so replace it by 100
 {[(66*3)+2]/3}/100

= (200/3)/100 
= (200/3)*(1/100) 
= 2/3 so its the simplest form 
hope it helps
HIGH SCHOOL

What is the domain of the given function? {(3, –2), (6, 1), (–1, 4), (5, 9), (–4, 0)}

{x | x = –4, –1, 3, 5, 6}
{y | y = –2, 0, 1, 4, 9}
{x | x = –4, –2, –1, 0, 1, 3, 4, 5, 6, 9}
{y | y = –4, –2, –1, 0, 1, 3, 4, 5, 6, 9}

Answers

Answer: Choice A) {-4, -1, 3, 5, 6}

The domain of a relation is the set of possible x inputs. All we do is list the x coordinates of the given points. The order doesn't matter but your book has decided to list the x values from smallest to largest.

Side note: the list of possible output y values is known as the range.

Answer:it’s answer A, or {x | x = –4, –1, 3, 5, 6}.

Step-by-step explanation:

COLLEGE

Rotating Light A searchlight rotates through one complete revolution every 4 seconds. How long does it take the light to rotate through 90°?

Answers

It takes 1 second. beep beep
Your Answer will be 84
MIDDLE SCHOOL

What is the solution to the system of equations represented by the two equations? y=3/2x y=-1/2x 4 (____,____)

PLEASE HELP AND AS SOON AS POSSIBLE 

Answers

If you are referring to simultaneous equations (which I think you are), you make the two equations equal to each other.

Since, y is equal to 3/2x and y is also equal to -1/2x + 4,

 3/2x must be equal to -1/2x + 4

=> 3/2x=-1/2x + 4
=> 3/2x + 1/2x = 4
=> 4/2x= 4
=> 2x= 4
=> x=2

If x= 2, you can substitute this value in either of the two initial equations to find the value for y :-

     y=3/2x
=> y=3/2*( 2)
=> y=3

So your two values for x and y are 2,3
Random Questions